The Effect of Publication Experience on Kompas.com for Writer’s Codes Ethics Analysis Ability and Reader’s Psychology - Wahyunengsih; Kya Dewi Davina (IJIP : Indonesian Journal of Islamic Psychology, 2023)
The ease of access offered by the internet makes many people choose to turn to online media as a source of information and news. One of the notable news media portals in Indonesia is Kompas.com. In conveying online news, Kompas.com journalists must, of course, pay attention to the journalistic ethical codes that have been regulated in the Press Law Number 40 of 1999. This research uses a qualitative approach with document analysis and note-taking methods. This study aims to answer whether the publication experience on Kompas.com affects the ability to analyze the author's code of ethics, what forms of violation of the journalistic code of ethics are found in Kompas.com's reporting and whether violations of the journalistic code of ethics can affect readers psychologically. The results of this study found that publication experience on Kompas.com did not affect the ability to understand the journalistic code of ethics. There are five forms of violations of the journalistic code of ethics that researchers found in Kompas.com news, and violations of the journalistic code of ethics can affect readers psychologically.